Achilles tendon rupture: Risk assessment for aerial and ground athletes - Wertz, J.; Galli, M.; Borchers, J. R. (Sports Health: A Multidisciplinary Approach, 2013)
Context: Achilles tendon (AT) rupture in athletes is increasing in incidence and accounts for one of the most devastating sports injuries because of the threat to alter or end a career. Despite the magnitude of this injury, reliable risk assessment has not been clearly defined, and prevention strategies have been limited. The purpose of this review is to identify potential intrinsic and extrinsic risk factors for AT rupture in aerial and ground athletes stated in the current literature.